NAT10 acetylates BCL-XL mRNA to promote the proliferation of multiple myeloma cells through PI3K-AKT pathway - Zhang, Yuanjiao; Deng, Zhendong; Sun, Shanliang; Xie, Siyuan; Jiang, Mingmei; Chen, Bing; Gu, Chunyan; Yang, Ye (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is a clinically distinctive plasma cell malignancy in the bone marrow (BM), in which epigenetic abnormalities are featured prominently. Epigenetic modifications including acetylation have been deemed to contribute to tumorigenesis. N-acetyltransferase 10 (NAT10) is an important regulator of mRNA acetylation in many cancers, however its function in MM is poorly studied. We first analyzed MM clinical databases and found that elevated NAT10 expression conferred a poor prognosis in MM patients. Furthermore, overexpression of NAT10 promoted MM cell proliferation. The correlation analysis of acRIP-seq screened BCL-XL (BCL2L1) as a significant downstream target of NAT10. Further RNA decay assay showed that increased NAT10 improved the stability of BCL-XL mRNA and promoted protein translation to suppress cell apoptosis. NAT10 activated PI3K-AKT pathway and upregulated CDK4/CDK6 to accelerate cellular proliferation. Importantly, inhibition of NAT10 by Remodelin suppressed MM cell growth and induced cell apoptosis. Our findings show the important role of NAT10/BCL-XL axis in promoting MM cell proliferation. Further explorations are needed to fully define the potential of targeting NAT10 therapy in MM treatment.